Pengaruh Digital Marketing, Goldilock Effect, dan Loyalitas Pelanggan Terhadap Keputusan Pembelian Online Pengguna Aplikasi Matahari - Kaetza, Rheyna Vallerina; Purnamasari, Devi (Jurnal EMT KITA, 2023)
Matahari department store which has innovated into the MatahariMall.com application as a digital marketing strategy to improve consumer purchasing decisions. This study aims to analyze the effect of digital marketing, goldilock effect and loyalty of purchasing decisions. This research method is quantitative with primary and secondary data sources. The data collection technique was carried out by distributing questionnaires to 100 samples taken by purposive sampling. Analysis of research data using multiple regression analysis. The results show that digital marketing has a significant positive effect on consumer purchasing decisions as evidenced by the t-count 5,411 and a significance of 0.000 <0.05. Goldilock effect has a significant positive effect on consumer purchasing decisions as evidenced by the t-count 3.818 and a significance of 0.000 <0.05. Consumer loyalty has a significant positive effect on consumer purchasing decisions as evidenced by the t value 2.353 and a significance of 0.021 <0.05.